Pengaruh Kualitas Produk, Citra Merek, Kepercayaan Merek, Celebrity Endorser, dan Getok Tular terhadap Minat Beli Produk Skincare Merek Ms Glow Di Daerah Istimewa Yogyakarta - Arif Sudaryana; Fitri Susilowati; Auriel Hanung Fidriana (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This study aims to analyze the effect of product quality, brand image, trusted brand, celebrity endorsers, and word of mouth on buying intention of MS Glow skin care products in the Special Region of Yogyakarta. This research examines MS Glow skin care products. The population of this study is the people in the Special Region of Yogyakarta who have used or purchased MS Glow products. Sampling was carried out by sampling technique using purposive sampling and using a questionnaire as a data collection method using a sample of 120 respondents. This type of research is quantitative. The results of this study indicate that product quality, brand image, brand trust, celebrity endorsers and word of mouth simultaneously have a positive and significant effect on the intention to buy MS Glow skin care products in the Special Region of Yogyakarta. Variables of product quality, brand image, brand trust, celebrity endorsers and word of mouth are able to explÂ  ain the purchase intention variable by 94,6% and the remaining 5,4% is explained by other variables not included in the study.